Comparison of efficiency for steel and combined frames - Bannikov, D; Nikiforova, N.; Leontiieva, I. (Ways to Improve Construction Efficiency, 2023)
Recently, in the practice of design, customers of design works and investors of various projects have a dilemma regarding the choice of building material for load-bearing building structures. At the same time, the choice is usually limited to two types of materials – steel and reinforced concrete. Each of these materials has its advantages and disadvantages, which results in their different efficiency of application for various types of building structures. At the same time, the main attention is paid to the estimation side, because in modern complex and dynamic conditions, it turns out to be dominant in many cases. The article presents the results of research of the completed master's thesis on the comparative analysis of the effectiveness of steel and combined frames (steel-reinforced concrete) on the example of the filter station building. The building has dimensions in plan of 54 × 36 m with a total height of about 22 m. Its supporting frame is a statically nondefined flat frame consisting of columns and crossbars in the form of trusses. In the longitudinal direction of the building, the frames are united into a spatial system by means of covering structures. The building is craneless and has three floors, each about 6.5 m high. In the course of research, the considered variants of the transverse frame were analyzed using the finite element method on the basis of the LIRA-CAD multifunctional design complex. As a result, appropriate cross-sections for loads according to the climatic conditions of Ukraine were obtained. A comparison of variants showed that the first design variant is 9 % cheaper. Taking into account the additional technological advantages in its manufacture, the steel frame can be considered more effective for the given construction conditions and be recommended for practical implementation. Separately, it should be noted that such a frame also has an average of 5 times less total mass, which should be considered its additional advantage.